Evaluation of Soluble CD48 Levels in Patients with Allergic and Nonallergic Asthma in Relation to Markers of Type 2 and Non-Type 2 Immunity: An Observational Study - Oded Breuer; Roopesh Singh Gangwar; Mansour Seaf; Ahlam Barhoum; Eitan Kerem; Francesca Levi-Schaffer (Journal of Immunology Research)
CD48 is a costimulatory receptor associated with human asthma. We aimed to assess the significance of the soluble form of CD48 (sCD48) in allergic and nonallergic asthma. Volunteer patients completed an asthma and allergy questionnaire, spirometry, methacholine challenge test, a common allergen skin prick test, and a complete blood count. sCD48, IgE, IL5, IL17A, IL33, and IFNγ were quantitated in serum by ELISA. Asthma was defined as positive methacholine challenge test or a 15% increase in FEV1 post bronchodilator in symptomatic individuals. Allergy was defined as positive skin test or IgE levels > 200 IU/l in symptomatic individuals. 137 individuals participated in the study: 82 (60%) were diagnosed with asthma of which 53 (64%) was allergic asthma. sCD48 levels were significantly elevated in patients with nonallergic asthma compared to control and to the allergic asthma cohort (median (IQR) pg/ml, 1487 (1338–1758) vs. 1308 (1070–1581), p<0.01, and 1336 (1129–1591), p=0.02, respectively). IL17A, IL33, and IFNγ levels were significantly elevated in allergic and nonallergic asthmatics when compared to control. No correlation was found between sCD48 level and other disease markers. sCD48 is elevated in nonallergic asthma. Additional studies are required for understanding the role of sCD48 in airway disease.